Review of Tenofovir Use in HIV-infected Children. Issue 4 (April 2015) - Aurpibul, Linda; Puthanakit, Thanyawee
Abstract : Tenofovir disoproxil fumarate (TDF) is approved by the Food and Drug Administration for use in children ages 2 years and older and is recommended by the World Health Organization for use as a preferred first-line nucleotide reverse transcriptase inhibitor in adults and adolescents ages 10 years and older. The simplicity of once daily dosing, few metabolic side effects and efficacy against hepatitis B virus make TDF suitable for use in a large scale program. Unlike thymidine analoge nucleoside reverse transcriptase inhibitors (NRTIs); tenofovir does not induce multi-NRTI resistance mutations, so more NRTI options are available for future second-line-regimens. Fixed-dose combinations of TDF with other ARVs as a single tablet regimen are now widely available for adults and adolescents, but none are available for young children. Current information on TDF including the pharmacokinetics, safety and tolerability in children and adolescents was reviewed. A dosing regimen according to body-weight-band has been established for pediatric use. Safety concerns of TDF mainly relate to its effects on renal function and bone mineral density. Regular monitoring of renal function in high-risk patients, including those on other nephrotoxic drugs, may be warranted to detect adverse renal effects. Long-term-data on renal and bone outcomes among HIV-infected children is needed. Lessons learned from clinical studies will help clinicians balance the risks and benefits of TDF and design appropriate antiretroviral regimens for children in different circumstances.